31 A multi-site retrospective case note review for clinical practices of constipation in specialist palliative care settings. Issue 3 (1st September 2018) - McIlfatrick, S; Muldrew, DHL; Carduff, E; Clarke, M; Coast, J; Finucane, A; Graham-Wisener, L; Hasson, F; Larkin, P; MacArtney, J; McCorry, N; Slater, P; et al.
Abstract : Background: Constipation is a common symptom for patients receiving palliative care. Whilst national clinical guidelines are available on the management of constipation for people with advanced cancer in specialist palliative care (SPC) settings questions exist around clinical practice and the extent to which the guidelines are implemented in practice. This study examine current clinical practice for management of constipation for patients with advanced cancer in SPC settings. Methods: A multi-site retrospective case-note review was conducted consisting of 150 patient case-notes from three SPC units across the United Kingdom between August 2016 and May 2017. Descriptive statistics were used to compare clinical practices to national policy guidelines for constipation. Results: A physical exam and bowel history was recorded for 109 patients (73%). Whilst the Bristol Stool Chart was used frequently across sites (96%) involvement of the multidisciplinary team varied. Almost a third of patient charts (27%) recorded no evidence of non-pharmacological management strategies. Pharmacological management was recorded frequently with sodium docusate or senna as the preferred laxatives across all sites however 33% of patient charts recorded no information on the titration of laxatives. There were no consistent management strategies recorded for opioid induced constipation or bowel obstruction Conclusion: Assessment and management of constipation in SPC settings is highly variable. Variations in assessment; limited use of non-pharmacological and preventative strategies and absence of consistent strategies for opioid induced constipation or bowel obstruction are evident. Further education is needed to equip HCPs with the necessary knowledge and skills to assess and manage constipation. References: . Friedrichsen M, Erichsen E. The lived experience of constipation in cancer patients in palliative hospital-based home care. Int J Palliat Nurs [Internet] 2004;10(7):321–5. Available from: http://search.ebscohost.com/login.aspx?direct=true&profile=ehost&scope=site&authtype=crawler&jrnl?=13576321&A?N=13991056&h=XKMF4r08srZuhDY0j7C95oLLyYKNHUcvoeEuhyXNnsIM2BI%2BEhmcY1pPP%2BN1pvrMzQ9Bn9b5j45X6WzyBRydEA%3D%3D&crl=c [Accessed: 21 August 2017] . Gilbert EH, et al. Chart reviews in emergency medicine research: Where are the methods?Annals of Emergency Medicine1996;27(3):305–8. Available at: http://www.ncbi.nlm.nih.gov/pubmed/8599488 [Accessed: 17 May 2018] . National Clinical Effectiveness Committee. Management of constipation in adult patients receiving palliative care national clinical guideline No. 10 November 2015. . Tvistholm N, Munch L, Danielsen AK. Constipation is casting a shadow over everyday life? A systematic review on older people's experience of living with constipation [Internet]. Journal of Clinical Nursing2017;26:902–14. Available from: http://doi.wiley.com/10.1111/jocn.13422 [Accessed: 21 August 2017] . Wickson-griffiths A, et al . Revisiting retrospective chart review: An evaluation of nursing home palliative and end-of-life care research. Palliative Medicine Care 2014;1(2):8. Available at: www.symbiosisonlinepublishing.com [Accessed: 23 November 2017]